Potential Use of Gluconate in Cancer Therapy - Mycielska, Maria E.; Mohr, Markus T. J.; Schmidt, Katharina; Drexler, Konstantin; Rümmele, Petra; Haferkamp, Sebastian; Schlitt, Hans J.; Gaumann, Andreas; Adamski, Jerzy; Geissler, Edward K. (Frontiers in Oncology, 2019)
We have recently discovered that cancer cells take up extracellular citrate through a plasma membrane citrate transporter (pmCiC) and advantageously use citrate for their metabolism. Citrate uptake can be blocked with gluconate and this results in decreased tumor growth and altered metabolic characteristics of tumor tissue. Interestingly, gluconate, considered to be physiologically neutral, is incidentally used in medicine as a cation carrier, but not as a therapeutically active substance. In this review we discuss the results of our recent research with available literature and suggest that gluconate may be useful in the treatment of cancer.